Rho-independent stimulation of axon outgrowth and activation of the ERK and Akt signaling pathways by C3 transferase in sensory neurons - Auer, Maria; Schweigreiter, Ruediger; Hausott, Barbara; Thongrong, Sitthisak; Höltje, Markus; Just, Ingo; Bandtlow, Christine; Klimaschewski, Lars (Frontiers in Cellular Neuroscience, 2012)
Peripheral nerve injury triggers the activation of RhoA in spinal motor and peripheral sensory neurons. RhoA activates a number of effector proteins including the Rho-associated kinase, ROCK, which targets the cytoskeleton and leads to inhibition of neurite outgrowth. Blockade of the Rho/ROCK pathway by pharmacological means improves axon regeneration after experimental injury. C3bot transferase, an exoenzyme produced by Clostridium botulinum, inactivates RhoA by ADP-ribosylation. Up to now it was not investigated thoroughly whether C3bot exerts positive effects on peripheral axon regeneration as well. In the present study, recombinant membrane permeable C3bot produced a small, but significant, axon outgrowth effect on peripheral sensory neurons dissociated from adult dorsal root ganglia of the rat. Neuronal overexpression of C3, however, did not enhance axonal growth. Moreover, transfection of plasmids encoding dominant negative RhoA or RhoA specific shRNAs failed to increase axonal growth. Furthermore, we show that the C3bot mutant, C3E174Q, which lacks RhoA inhibitory activity, still stimulates axonal growth. When analyzing possible signaling mechanisms we found that ERK (extracellular signal-regulated kinase) and Akt are activated by C3bot and ERK is induced by the C3E174Q mutant. Upregulation of kinase activities by C3bot occurs significantly faster than inactivation of RhoA indicating a RhoA-independent pathway of action by C3bot. The induction of ERK signaling by C3bot was detected in embryonic hippocampal neurons, too. Taken together, although RhoA plays a central role for inhibition of axon outgrowth by myelin-derived inhibitors, it does not interfere with axonal growth of sensory neurons on a permissive substrate in vitro. C3bot blocks neuronal RhoA activity, but its positive effects on axon elongation and branching appear to be mediated by Rho independent mechanisms involving activation of axon growth promoting ERK and Akt kinases.